Part A:
4x + 2(x − 3) = 4x + 2x − 11
4x + 2x - 6 = 4x + 2x - 11
6x - 6 = 6x - 11
-6 = -11
There are no solutions because -6 is not equal to -11.
Part B:
I used the Distributive Property to simplify the equation by multiplying 2 to both terms inside the parentheses.
An equation is shown below:
4x + 2(x − 3) = 4x + 2x − 11
Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points)
Part B: Name one property you used to solve this equation.
(less than 50 words for each and make it sound like a fifth grader)
1 answer